Determination of fluoroquinolones in milk, honey and water samples by salting out-assisted dispersive liquid-liquid microextraction based on deep eutectic solvent combined with MECC. (1st December 2020) - Yu, Kaili; Yue, Mei-E.; Xu, Jie; Jiang, Ting-Fu
Highlights: The SO-DLLME combined with MECC was developed for determination of fluoroquinolones. Deep eutectic solvent (DES) was used as an extraction solvent combined with back extraction. A detection limit less than 10 ng mL −1 for fluoroquinolones could be achieved. The method was successfully applied to determination of fluoroquinolones in food and water samples. Abstract: A simple and sensitive salting out-assisted dispersive liquid-liquid microextraction method using deep eutectic solvent combined with back extraction and micellar electrokinetic capillary chromatography (SO-DLLME-DES-BE-MECC) was developed for the determination of fluoroquinolones in milk, honey and water samples. Several parameters affecting the extraction efficiency including DES volume, vortex time, centrifugation time, salt type and amount, sample pH and volume, etc. were investigated. Good linearity were obtained for fluoroquinolones in a range of 0.020–3.200 μg mL −1 and 0.030–4.800 μg mL −1 with LODs less than 0.010 μg mL −1 . The recoveries were in the ranges of 95.0–104.9%, 90.1–110.2% and 87.8–114.1% for water, honey and milk samples, respectively. The relative standard deviations for reproducibility were all below 7.6%. Under the optimized conditions, the enrichment factors for analytes were achieved in the range from 531 to 858 folds. The presented method was successfully applied for the determination of fluoroquinolones in milk, honey and water samples.